Kepastian Hukum dalam Pengujian Formil Undang-Undang oleh Mahkamah Konstitusi di Indonesia terkait Inkonsistensi Putusan, Batas Waktu Pengujian, dan Implikasi Pembatalan Undang-Undang - Bhakti, Teguh Satya (LPPM Institut Pendidikan Nusantara Global, 2025)
The Constitutional Court of Indonesia holds the authority to conduct a formal judicial review to ensure that the legislative process complies with the 1945 Constitution. However, legal certainty in this mechanism remains problematic due to inconsistent rulings, unclear time limits for filing, and complex implications of law annulment. These issues highlight the urgent need to re-examine the effectiveness of formal judicial review as a constitutional safeguard. This research employs a normative juridical method, combining statutory, conceptual, and case approaches. Legal materials are drawn from the 1945 Constitution, the Constitutional Court Law, Constitutional Court Regulations, and relevant rulings, supported by scholarly opinions. The study specifically analyzes three landmark cases: Decision No. 27/PUU-VII/2009, Decision No. 79/PUU-XX/2022, and Decision No. 91/PUU-XVIII/2020, to explore the dimensions of inconsistency, procedural deadlines, and the effects of annulment. The findings indicate that the Constitutional Court has not established consistent jurisprudence regarding the admissibility of petitions, particularly in relation to time frames and procedural defects. Furthermore, the adoption of the “conditionally unconstitutional” model in annulling laws creates legal uncertainty for governance and law enforcement. The study concludes that clearer legal frameworks and consistent jurisprudence are essential to strengthen legal certainty in formal judicial review in Indonesia.